Major histocompatibility complex class I-restricted cytotoxic T-lymphocyte responses in horses infected with equine herpesvirus 1. - Allen, G (1995)
An experimental system that permits sensitive and reproducible detection of equine herpesvirus 1 (EHV-1)-specific cytotoxic T-lymphocyte (CTL) activity in the horse was developed. Peripheral blood mononuclear cells (PBMC) collected from immune horses were restimulated in vitro by culture with live EHV-1. Cytotoxic activity against virus-infected, pokeweed mitogen-stimulated lymphoblast targets was assessed in a 4-h 51Cr release assay. The optimal conditions for in vitro stimulation of equine memory CTLs and for preparation of EHV-1-infected target cells expressing viral antigens were systematically identified by individually testing the effects of variations in responder cell concentration, culture medium composition, serum type, incubation time, antigen form, and exogenous mediator content. By using this optimized system for generation and assay of equine CTLs, the development of EHV-1-specific cytotoxic responses in 12 horses was evaluated after experimental viral infection. CTLs with the capacity for killing EHV-1-infected target cells were detected in equine PBMC as early as 1 week postinfection, reached maximal levels by 2 to 3 weeks, and remained detectable for a year after infection. Equine effector cells mediating lysis of EHV-1-infected targets were predominantly CD8+ T lymphocytes, and the cytotoxicity was specific for virus and restricted by major histocompatibility complex class I molecules. The results define a reliable and convenient experimental system for generation and assay of EHV-1 CTLs which can now be used for more-detailed characterization of the equine CTL response to infection by this herpesvirus pathogen.